Malaysian freelance software developer development practice: a preliminary study / Mohd Akmal Faiz Osman, Mohamad Noorman Masrek and Khalid Abdul Wahid - Faiz Osman, Mohd Akmal; Masrek, Mohamad Noorman; Abdul Wahid, Khalid (Faculty of Information Management, 2022)
Freelance developers are highly skilled individuals hired by software development organizations to assist with development jobs. The lack of literature regarding the development practices of freelance developers has prompted this preliminary study to be conducted. Interviews with seven professional freelance developers have been conducted, and thematic analysis was performed on the data obtained. The results show that freelance developers do not strictly follow any commercial system development methods because of their rigidity and time-consuming. Freelance developers were found to utilize their expertise to incorporate reusable software assets during development to save on time and cost. This study discusses the current development practices that are employed by Malaysian freelance developers in the development of software.